Technology, Dementia and Ethics: Rethinking the Issues - Baldwin, Clive (Disability Studies Quarterly, 2005)
Although there has been a marked increase in interest in using and developing technology in dementia care, discussion regarding the ethical issues of that development and application is severely limited. Discussion is limited both in scope — the issues that are deemed suitable for ethical reflection — and in the paradigm within which those limited issues are discussed, namely the dominance of the principlist approach to bioethics. This paper offers a series of reflections on technology, dementia and ethics in an attempt to widen the debate and generate new ways of thinking about the issues involved in the development and application of technology in the field of disability generally.